Review: the effects of dust on feedlot health and production of beef cattle. Issue 1 (1st January 2021) - Urso, Phil M.; Turgeon, Abe; Ribeiro, Flavio R. B.; Smith, Zachary K.; Johnson, Bradley J.
ABSTRACT: Dust in feedlots is detrimental to optimal cattle performance. Contributors such as climate, manure production, and animal behaviour can affect dust production and ultimately, cattle health. Bovine respiratory disease (BRD) and acute interstitial pneumonia (AIP) represented to 68% of death loss across 30 feedyards from 2015 to 2017. Bovine respiratory disease specifically costs producers between 800 and 900 million each year with the cost per animal varying based on number of treatments, occurrence, and performance differences. Altering feeding schedule, stocking density, and sprinkler systems have decreased dust concentrations. By using these methods, cattle feeders can limit dust production and promote animal health. This paper serves to consolidate previous research and data discussing the effects of dust on cattle health.